2021
DOI: 10.1177/17470218211008060
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of cognitive offloading: Boosting performance but diminishing memory

Abstract: Modern technical tools such as tablets allow for the temporal externalization of working memory processes (i.e. cognitive offloading). Although such externalizations support immediate performance on different tasks, little is known about potential long-term consequences of offloading behavior. In the current set of experiments, we studied the relationship between cognitive offloading and subsequent memory for the offloaded information as well as the interplay of this relationship with the goal to acquire new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 68 publications
1
29
0
1
Order By: Relevance
“…However, Runge et al (2020) also documented a mnemonic cost for the saved material: participants recalled fewer of the items that they were able to save to a computer than those that they could not save. There are other conditions in which offloading items to external storage can impair memory for the offloaded items on a delayed memory test, but people who are aware that there will be a delayed test can largely overcome the detrimental effects of offloading on long-term memory (Grinschgl et al 2021).…”
Section: Internet and Computer Effectsmentioning
confidence: 99%
“…However, Runge et al (2020) also documented a mnemonic cost for the saved material: participants recalled fewer of the items that they were able to save to a computer than those that they could not save. There are other conditions in which offloading items to external storage can impair memory for the offloaded items on a delayed memory test, but people who are aware that there will be a delayed test can largely overcome the detrimental effects of offloading on long-term memory (Grinschgl et al 2021).…”
Section: Internet and Computer Effectsmentioning
confidence: 99%
“…Other costs of using reminders may only become apparent in the long run. That is, apart from needing more time and effort, individuals miss out important cognitive exercise when setting up a reminder, possibly affecting cognitive functioning eventually (see Grinschgl et al, 2021b ). In fact, the human brain is highly plastic (Green & Bavelier, 2008 ), requiring exercise to establish and maintain proper functioning, especially at an older age (Buckner, 2004 ; Joubert & Chainay, 2018 ; Morrison & Chein, 2011 ; Park & Bischof, 2013 ; Small, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in offloading due to modern technologies, the question arises whether offloading is accompanied by positive and/or negative consequences. Cognitive offloading was shown to improve immediate task performance by accelerating it and/or reducing errors (e.g., Boldt and Gilbert, 2019 ; Grinschgl et al, 2021b ). Furthermore, studies showed that offloading improves simultaneous secondary task performance (Grinschgl et al, 2022 ) and later performance of unrelated tasks (Storm and Stone, 2015 ; Runge et al, 2019 ).…”
Section: Overview Of Cognitive Offloading With Modern Technologiesmentioning
confidence: 99%
“…Importantly, cognitive offloading is also accompanied by risks. In three experiments, Grinschgl et al ( 2021b ) observed a trade-off for cognitive offloading: while the offloading of working memory processes increased immediate task performance, it also decreased subsequent memory performance for the offloaded information. Similarly, the offloading of spatial processes by using a navigation device impairs spatial memory (i.e., route learning and subsequent scene recognition; Fenech et al, 2010 ).…”
Section: Overview Of Cognitive Offloading With Modern Technologiesmentioning
confidence: 99%
See 1 more Smart Citation